Laparoscopic treatment of abdominal wall endometriosis: A case series - Jinbo Li; Lingbing Qiu; Xiao Li; Taicheng Zhou; Shuqin Chen (Case Reports in Women's Health, 2024)
Objective: This report summarizes the characteristics of a series of 8 recent (2020−2022) patients with abdominal wall endometriosis (AWE) who underwent laparoscopic surgery. The feasibility and advantages of laparoscopy in the treatment of AWE are set out. Methods: The clinical data of the 8 AWE patients were retrospectively analysed. Basic clinical characteristics, operation details and postoperative details were collected and analysed. Results: Laparoscopic treatment was successful in all 8 cases. The mean operation time was 212.13 ± 48.16 min, the mean estimated blood loss was 25.00 ± 11.18 ml, and the mean postoperative hospital stay was 5.25 ± 1.39 days. 7 of the patients were found to have concomitant pelvic endometriosis, and 1 patient was found to have concealed inguinal hernias during surgery. Concomitant laparoscopic surgery for pelvic lesions was performed, including electrocautery or lesion resection of the pelvic endometriosis lesions in 7 patients, uterine fibroidectomy in 2 patients, high ligation of the hernia sac in 1 patient and endometrial biopsy under hysteroscopy in 1 patient. Endometrial-like tissue was confirmed by postoperative pathological examination of resected AWE lesions in all patients. There were no intraoperative or postoperative complications. The mean follow-up time was 18.75 ± 3.96 months, and no recurrence of AWE was found. Conclusion: Laparoscopic surgery is a safe, effective and feasible treatment option for AWE patients and has the advantages of simultaneous diagnosis and treatment of other pelvic lesions.